2012
DOI: 10.2478/v10011-012-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Deaminase Isoenzymes in the Diagnosis and Monitoring of Rheumatoid Arthritis

Abstract: The aim of this study was determination of the cata ly tic activities of adenosine deaminase (ADA), ADA1 and ADA2 isoenzymes in the serum of patients suffering from rheumatoid arthritis (RA) who were and were not treated with methotrexate (MTX), and identification of the possibilities of using these biochemical parameters in diagnosing and monitoring the treatment effects in RA. Catalytic activities of total ADA (tADA) and ADA2 in serum were determined by a spectrophotometric method. A statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 23 publications
3
42
2
Order By: Relevance
“…In this regard, serum YKL-40 levels increase even in early RA patients (22,33). In a recent study, it has been proposed that a »multi-biomarker disease activity score« which was calculated using the concentrations of twelve biomarkers, including YKL-40, measured disease activity (34,35). However, as seen in the present study, the low sensitivity of serum YKL-40 for RA might be an obstacle to its clinical use.…”
Section: Discussioncontrasting
confidence: 48%
“…In this regard, serum YKL-40 levels increase even in early RA patients (22,33). In a recent study, it has been proposed that a »multi-biomarker disease activity score« which was calculated using the concentrations of twelve biomarkers, including YKL-40, measured disease activity (34,35). However, as seen in the present study, the low sensitivity of serum YKL-40 for RA might be an obstacle to its clinical use.…”
Section: Discussioncontrasting
confidence: 48%
“…Studies conducted to evaluate the role of ADA in patients with rheumatoid arthritis showed varied results. Nalesnik M et al, reported significant correlation between ADA and CRP in patients with RA without methotrexate treatment and suggested that ADA activity in serum can be used as a biochemical marker of the inflammatory process in RA [16]. In an earlier study, Yuksel and colleague [17] measured serum and synovial fluid ADA activity in patients with Rheumatoid arthritis, osteoarthritis and reactive arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme ADA represents a checkpoint in the regulation of extra cellular Adenosine levels [8] and thus is likely to modulate the inflammatory processes. Hence, although determination of serum adenosine levels is an appropriate way to assess disease activity in RA [8], ADA also seems to be a prediction marker of the inflammatory process in RA [16]. In this context, Zamani et al, [21] studied the relationship between serum adenosine deaminase and disease activity and concluded that a new disease activity index applying serum ADA helps in predicting disease activity in RA.…”
Section: Discussionmentioning
confidence: 99%
“…The autoantibodies and high level of inflammatory markers help in diagnosis while they are also important for prognosis and diagnosis of treatment. 3 The biological markers such as acute phase reactants, rheumatoid factor (RF) etc. acts as an indicator of the disease progression besides the number of swollen and tender joints.…”
Section: 2mentioning
confidence: 99%